E-Commerce and Industrial Upgrading in the Chinese Apparel Value Chain. Issue 1 (1st January 2019) - Li, Fuyi; Frederick, Stacey; Gereffi, Gary
ABSTRACT: The economic and social gains from electronic commerce (e-commerce) that promote innovation, industry upgrading and economic growth have been widely discussed. China's successful experience with e-commerce has had a positive effect in transforming consumer-goods sectors of the economy and motivating economic reform. This article looks at how e-commerce reduces barriers to entry and enables firms to move up the value chain by using the global value chain framework to analyse the impact of e-commerce on the upgrading trajectories and governance structures of China's apparel industry. For large Chinese brands, e-commerce has enabled end-market diversification. For small- and medium-sized enterprises, e-commerce has facilitated entry with functional upgrading as well as end-market upgrading. In the "two-sided markets" created by platform companies, the "engaged consumers" are the demand side of this market, and "e-commerce focused apparel firms" are the supply side of the new market. Consumers and platforms are more directly involved in value creation within this emerging internet-based structure.